2022
DOI: 10.1155/2022/1251388
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Computer-Based Simulation Teaching Combined with PBL in Colorectal Tumor Hemorrhage

Abstract: Objective. This paper aims to explore the use of computer-based simulation teaching combined with PBL in colorectal tumor bleeding. Methods. The outpatient department organized 21 nursing staffs to conduct computer simulation combined with PBL teaching, compared emergency theory and skill scores, and investigated the recognition of computer simulation teaching combined with PBL. Results. The scores of theoretical knowledge examination before training were (84.31 ± 6.39) and (92.59 ± 2.93) after training; the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…SPSS20.0 statistical software was used for analysis, mean + standard deviation ( x ± s) for measurement data, t-value check, rate (%) for count data, X2 check, when P < 0.05, the difference between the two groups of data is statistically significant [10]. DOI: https://doi.org/10.31058/j.edu.2023.71017 Submitted to Education Journal, page 156-159 www.itspoa.com/journal/edu…”
Section: Statistical Processingmentioning
confidence: 99%
“…SPSS20.0 statistical software was used for analysis, mean + standard deviation ( x ± s) for measurement data, t-value check, rate (%) for count data, X2 check, when P < 0.05, the difference between the two groups of data is statistically significant [10]. DOI: https://doi.org/10.31058/j.edu.2023.71017 Submitted to Education Journal, page 156-159 www.itspoa.com/journal/edu…”
Section: Statistical Processingmentioning
confidence: 99%
“…Compared with actual clinical cases, when the patient's hemodynamics change significantly, anesthesiology students will have confusion in thinking and behavior, and even cannot be quickly and skillfully treated urgently. For such patients, during the treatment period, the regular training teachers cannot directly let the anesthesia trainees carry out separate treatment, which makes it difficult for anesthesia inpatient medical students to carry out practical operations, and their ability to improve their personal emergency treatment ability is not obvious, and even cannot face the management of critically ill patients during surgery alone [3] .…”
Section: Trainees Have Little Practical Knowledgementioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%